MANAJEMEN RISIKO PEMBERIAN KREDIT TANPA AGUNAN UNTUK MENGURANGI RISIKO KREDIT DI PT. BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG UTAMA FATMAWATI - Tedi Rochendi (Institut Teknologi dan Bisnis Swadharma, 2020)
Credit Risk is a risk of loss caused by the inability (default) of the debtor to pay his debts, both principal and interest, or both. Loss risk is a loss that occurs as a direct or indirect consequence of a risk event. At PT. Bank Negara Indonesia (Persero) Tbk Fatmawati Main Branch Office credit problems are still often found and mitigation is something that affects the achievement of the goals of PT. BNI (Persero) Tbk KCU Fatmawati. If the risk cannot be properly mitigated, the welfare of the bank will be disturbed. The risk factor for loss can be caused by two things, namely the risk of loss caused by the customer deliberately not wanting to pay his credit even though he is able and the risk of loss due to the customer accidentally, namely due to disasters such as natural disasters, fires and others. The cause of not being collected is due to a grace period for repayment (period). The longer the term of a credit, the greater the risk of being uncollectible, and vice versa. This risk is the responsibility of the bank, both intentional and unintentional.